Evaluation of Phytochemical Components and Antidiarrheal Activity of Hydro-Methanolic Extracts of Carica papaya Seeds in Castor Oil-Induced Diarrhea in Wistar Rats (Journal of Environmental Microbiology and Toxicology, 2024)
Carica papaya, popularly known as pawpaw in English, is a plant that grows worldwide and bears leaves, fruits, and seeds with many medicinal properties, including anti-inflammatory, antidiarrheal, and antibiotic effects. The seeds of Carica papaya were collected at Dandagoro Garden and authenticated by a botanist at Ummaru Musa Yar'adua University, Katsina, with voucher number UMYUK/P/105.This study aimed to evaluate the antidiarrheal activity of the hydro-methanolic extract of Carica papaya seeds in Wistar rats using a negative and positive control. The seed extract was administered to Wistar rats (weighing 162 g) at different doses in each of the five groups, each containing five Wistar rats. Thirty minutes after the administration of the extracts, diarrhea was induced using castor oil. The quantitative determination of phytochemical constituents in Carica papaya seeds was performed using a UV spectrophotometric method. The results shows that alkaloids having the highest amount of (24.03±0.08 mg/100 g) whereas tannins having the lesser amount (0.02±0.01 mg/100 g), also the antioxidant activities of Carica papaya seed extract and its effects on some biomarkers where determined which includes the Intestinal Protein (IP), malondialdehyde (MDA), reduced glutathione(GSH), superoxide dismutase(SOD), alkaline phosphatase (AP), nitric oxide (NO) and Na+-K+ ATPase. The levels of IP, SOD and AP shows a significant decrease when compared to the negative control at (p≤0.05). The levels of NO, GSH, and Na+-K+ ATPase show a significant increase compared to the negative control (p ≤ 0.05). The levels of MDA do not show any significant increase or decrease when compared to the negative control (p ≥ 0.05). In conclusion, the findings of this study show that Carica papaya seeds have antidiarrheal properties, albeit in a lesser amount, which may be due to their lower flavonoid content. However, Carica papaya seeds can be used to control diarrhea before an absolute proper medication.
Keywords: Carica papaya seed; Wistar rats; Antidiarrheal; Laperomide; Antibiotic